119k views
5 votes
Determine the solution to the system of equations below: y = -3x + 6 and 3y = -2x - 3

1 Answer

14 votes

Answer:

x = 3

y = -3

Explanation:

We have two equations and are asked to solve for x and y.

y = -3x + 6

3y = -2x - 3

Substitute the y in the first equation in the second equation :

3(-3x + 6) = -2x - 3

Distribute :

-9x + 18 = -2x - 3

Solve for x by isolating it :

Subtract 18 from both sides :

-9x = -2x - 21

Add 2x to both sides :

-7x = -21

Divide -7 from both sides :

x = 3

Replace x in the first equation :

y = -3(3) + 6

y = -9 + 6

-9 + 6

y = -3

User Starling
by
5.1k points